Development of Culturally Responsive Teaching-Learning Model Differentiated Learning to Improve Computational Mathematics Skills - Kurniasi, Eka Rachma; Nurrahmah, Arfatin; Suhendri, Heri; Hartati, Leny (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2025)
The study aims to develop a Culturally Responsive Teaching (CRT) learning model for differentiated learning to improve students' computational thinking skills. The urgency is based on research stating the low computational thinking skills. The importance of the culturally responsive teaching approach as a learning model and its application to differentiated learning in the independent curriculum. The type of development research with the ADDIE model development research design. The steps are Analysis, Design, Development or production, Implementation, and Evaluation. The product of the Culturally Responsive Teaching learning model development is differentiated learning in mathematics as an innovation and is applied to improve computational thinking skills. The research subjects were students of SMP Citra Nusa Cibinong. Data collection instruments were expert validation sheets, observation sheets, interview sheets, student response questionnaires, teachers and five essay-style mathematical computational thinking ability test questions. Data analysis techniques were quantitative and qualitative data analysis. The results of the study were a valid and practical CRT learning model for differentiated learning. The learning model was in groups with group divisions based on the ethnic background of the students and then given learning media in the form of LKPD where each story in the LKPD is different, namely Sundanese Tribe, Javanese Tribe, Minang/Padang Tribe, Betawi Tribe. The increase in mathematical computational ability based on the normalised gain test is 0.49 in the medium category (n-gain criteria 0.3<n-gain?0.7).